2016
DOI: 10.1097/phm.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Dry Needling and High-Power Pain Threshold Ultrasound Therapy with Clinical Status and Sonoelastography in Myofascial Pain Syndrome

Abstract: Our study favors the efficacy of both treatment methods in myofascial pain syndrome. Although a significant decrease was shown in tissue stiffness with HPPT, neither of these treatments had an apparent superiority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Three hundred and twenty-four ( n = 324) studies remained after removing duplicates. Two hundred and ninety-five ( n = 295) were excluded after the analysis of titles and/or abstracts, leaving 29 articles for final full-text review [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. One article [ 34 ] was excluded because the comparator was acupuncture intervention and the placebo used laser.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three hundred and twenty-four ( n = 324) studies remained after removing duplicates. Two hundred and ninety-five ( n = 295) were excluded after the analysis of titles and/or abstracts, leaving 29 articles for final full-text review [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. One article [ 34 ] was excluded because the comparator was acupuncture intervention and the placebo used laser.…”
Section: Resultsmentioning
confidence: 99%
“…Post-needling soreness was the most common adverse event and was reported in 53% (8/15) of the trials [ 27 , 28 , 32 , 38 , 40 , 43 , 45 , 48 ] and resolved spontaneously in 24–48h without further treatment. Thirteen (47%, n = 13/28) of the included studies [ 23 , 24 , 25 , 30 , 35 , 36 , 42 , 44 , 46 , 47 , 48 , 49 , 51 ] did not report any information about adverse events ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…La punción seca propuesta por Travell y Simons ha sido comparada con la inyección anestésica (Ay, Evcik, & Tur, 2010), con los efectos del ultrasonido (Aridici et al, 2016) y con la técnica de estimulación intramuscular paraespinal (Ga, Choi, Park, & Yoon, 2007), en todos los casos se ha demostrado disminución en los niveles de dolor con el uso de la punción seca de Travell y Simons. En comparación con la inyección anestésica no se observaron diferencias significativas, en ambos grupos se disminuyeron los niveles de dolor y aumentaron los rangos de movimiento, (valor P <.001) (Ay, Evcik, & Tur, 2010); en comparación con los efectos del ultrasonido no hay diferencias significativas, en ambas se observa disminución de los niveles de dolor, de discapacidad de cuello y de número de puntos dolorosos, el valor P para ambas intervenciones fue <0,05 (Aridici et al, 2016); y con respecto a estimulación la intramuscular paraespinal ambas intervenciones revelan disminución del dolor y ROM cervical pasivo en movimientos de flexión e inclinación, así es que no hay diferencias significativas entre ambas técnicas (valor P para ambos fue de p<0.001) (Ga, Choi, Park, & Yoon, 2007) En el subgrupo de punción seca implementada con tubo guía se clasifican los estudios que para realizar la técnica de punción seca usaron un tubo guía para introducir la aguja. De nuevo se resaltan los estudios de comparación de esta técnica con otras.…”
Section: Artículo 06unclassified
“…Some authors have suggested that the application of DN could regulate muscle tone and modify hypertonia, spasticity and certain musculoskeletal disorders. 10,11 Proposed mechanisms include modification of muscle stiffness and viscoelastic properties, [12][13][14] and modulation of neurophysiological activity within the spinal cord. [15][16][17][18] Muscle stiffness is defined as the ratio of the change in resistance to the change in length 19 and is a muscle property that is related to extensibility and performance.…”
Section: Introductionmentioning
confidence: 99%
“…20 All these properties, together with neurogenic factors, characterise muscle tone. However, very few studies have analysed the specific effects of DN on muscle stiffness and motoneuron excitability, [12][13][14][15][16][17][18] and none of them have compared the effects of DN when needling two different locations in a controlled way. Thus, the objective of this study was to analyse the biomechanical (muscle stiffness, extensibility and isometric strength) and neurophysiological (soleus H-reflex) effects in two different locations of the MTrP area (the nodule and the TB).…”
Section: Introductionmentioning
confidence: 99%